Manuscripts al-Taysir Fi al-Tafsir by Abu al-Barakat Muhammad Badr al-Din al-Ghazzi: A study on surah al-Fatihah and the opening of surah al-Baqarah / Ibrahim Abdullah Salih Muhamadi - Ibrahim Abdullah, Salih Muhamadi (2018)
This research is a study about a manuscript called Al-Taysir fi Al-Tafsir, it was wrote by Imam Badr Al-Din Al-Ghazzi. The objective of this study is to verify this manuscript. It has a certain significance, as it is unique, for it was the first time the holy Quran explained in such a unique way as no one else done it before him. The researcher followed analytical way according to comprehensive verification. The research came with introductory preamble, and 5 Chapters. The researcher talked about manuscript verification means and bases, Islamic manuscripts and their importance, and the importance of poetry in Islamic Folklore. Then talked about the author and his life and works, then about legality or legitimacy of interpreting the holy Quran by means of poetry, then explain about manuscript copies and its importance and the author way of conducting his work, finally he verified the poetry reflecting the actual work of study. The researcher did come with some important results, and gave some tips and advises regarding this study. One of the results is: This transcript belongs truly to the author Al-Ghazzi. Also that this copy of the name “A” had not copied from the original copy, so as the second copy that we have named “B”. Both copies A and B copied from different copies, as each one contains few fraises not found in the other one. The researcher has mentioned few tips to get better benefits of the research; one of them is to verify the rest of “Al-Baqarah chapter”, as well as the rest of chapters of the holy Quran. The second is to try to make available more copies that are different then what we have, named A and B, that hopefully have more Chapters of the holy Quran. To have intensive courses to researchers and students about transcript’s verification showing its importance and rules. Finally, to include a subject called “Transcript’s Verification” to bachelor and postgraduates’ curriculum.